2022
DOI: 10.3389/fonc.2022.867702
|View full text |Cite
|
Sign up to set email alerts
|

Values of MRI Imaging Presentations in the Hepatobiliary Phase, DWI and T2WI Sequences in Predicting Pathological Grades of Intrahepatic Mass-Forming Cholangiocarcinoma

Abstract: ObjectiveTo retrospectively investigate the value of various MRI image menifestations in the hepatobiliary phase (HBP), DWI and T2WI sequences in predicting the pathological grades of intrahepatic mass-forming cholangiocarcinoma (IMCC).Materials and MethodsForty-three patients of IMCCs confirmed by pathology were enrolled including 25 cases in well- or moderately-differentiated group and 18 cases in poorly-differentiated group. All patients underwent DWI, T2WI and HBP scan. The Chi square test was used to comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…The degree of pathological differentiation is an important prognostic indicator for ICC, with poorer differentiation indicating a worse prognosis [10] . Studies on preoperative imaging to predict the degree of histological differentiation of ICC reported several independent risk factors for predicting poorly differentiated ICC, including the presence of an incomplete hypointense rim in the MRI hepatobiliary phase, intrahepatic metastases, absence of centripetal lling of contrast agent in lesions in the portal venous and delayed phases, larger tumor diameters, and higher PET/CT SUVmax and tumor-to-normal liver tissue ratio (TNR) [8,11] . However, our study found no statistically signi cant differences in CT imaging signs between ICCs with the three histological differentiations.…”
Section: Discussionmentioning
confidence: 99%
“…The degree of pathological differentiation is an important prognostic indicator for ICC, with poorer differentiation indicating a worse prognosis [10] . Studies on preoperative imaging to predict the degree of histological differentiation of ICC reported several independent risk factors for predicting poorly differentiated ICC, including the presence of an incomplete hypointense rim in the MRI hepatobiliary phase, intrahepatic metastases, absence of centripetal lling of contrast agent in lesions in the portal venous and delayed phases, larger tumor diameters, and higher PET/CT SUVmax and tumor-to-normal liver tissue ratio (TNR) [8,11] . However, our study found no statistically signi cant differences in CT imaging signs between ICCs with the three histological differentiations.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, these findings are not specific and can be identified even in other neoplastic lesions, such as adenocarcinoma metastases [ 50 ]. For this purpose, Xing et al tried to define the MRI features predicting mass-forming iCCA in 43 patients with histopathological diagnosis and different degrees of differentiation: the presence/absence of intrahepatic metastases; the grade of the integrity of the hypointense ring in the hepatobiliary phase; and the target sign in T2-weighed sequences were highlighted as independent factors in the identification of differentiation degree of mass-forming iCCAs [ 51 ].…”
Section: Introductionmentioning
confidence: 99%
“…Given the indispensable role of imaging in MICC management, investigators have attempted to explore non-invasive imaging biomarkers for accurate differential diagnosis as well as prediction of pathological grade and subtype. [10] , [11] , [12] Studies have also documented the potential prognostic value of radiological traits at dynamic computed tomography (CT)/magnetic resonance (MR) imaging for patients with MICC. [13] , [14] , [15] However, the progress toward clinical translation has been slower than anticipated despite extensive investigations.…”
Section: Introductionmentioning
confidence: 99%